Design of a functional medical device for home monitoring - Eker, Kadir; Kiymik, M. Kemal (IEEE, 2016)
In this study, biomedical devices which is used by patient at home such as glucometer, thermometer, blood pressure meter intended to be performed with the functions of a single device. Biological signals such as blood pressure, blood sugar and body temperature can be measured and the measurement results can be recorded with proposed system. Oscillometric method is preferred for blood pressure measurement, thereby making it possible to measure hypotension and hypertension levels. MLX90614 non-contact temperature sensor used for measuring the body temperature, the electrochemical test strip is used for measuring blood sugar. Designed system gets real time clock information utilizing DS 1307 module. Thus, the time and date information with each measurement is also recorded on the micro SD card. The system basically consist of arduino mega card, 3.6 inch touch screen, pressure sensor, non-contact temperature sensors, electrochemical test strip, battery, micro SD cards, motor and valve driver circuit, real-time clock module, filter stage and current-voltage converter circuit.